Supported monatomic catalyst as well as preparation method and application thereof

By impregnating the nanoporous metal oxide into metal salts and heat treatment, a single-atom catalyst that depends on surface chemical bonds is formed, the problem of low loading of single-atom catalysts is solved, high loading and stability are achieved, and catalytic activity is improved.

CN119259074APending Publication Date: 2025-01-07SHANGHAI JIAOTONG UNIV +1

Patent Information

Application Number
CN202411258396.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-09
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

The loading of existing single-atom catalysts is low, which leads to easy aggregation of metal atoms, reduces catalytic activity, and depends on defect sites on the support surface, limiting the increase in loading.

Method used

By impregnating the nanoporous metal oxide into the metal salt precursor solution and heat treatment, a metal single atom catalyst is formed. The metal atoms are anchored by bonding with oxygen on the surface of the nanoporous metal oxide support, forming incomplete fractured chemical bonds to avoid Atoms aggregate and increase load.

Benefits of technology

High metal single atom loading and stability are achieved, the dependence on the support defect sites is avoided, and catalytic activity is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119259074A_ABST
    Figure CN119259074A_ABST
Patent Text Reader

Abstract

The invention provides a supported monatomic catalyst as well as a preparation method and application thereof, and the preparation method of the monatomic catalyst comprises the following steps: dipping a nano-porous metal oxide in a precursor solution of metal salt to obtain the metal salt supported on the nano-porous metal oxide; and carrying out heat treatment on the metal salt loaded on the nano-porous metal oxide, and decomposing to obtain the metal monatomic catalyst loaded on the nano-porous metal oxide. Metal salt loaded on the porous metal oxide is subjected to heat treatment, so that chemical bonds on the surfaces of metal atoms are not completely broken, the metal atoms are kept in a relatively isolated state to form single atoms, and meanwhile, the metal atoms are anchored through oxygen bonds on the surface of the nano porous metal oxide carrier; the metal single atom formed by the method is isolated by depending on the surface incompletely broken chemical bond and does not depend on the number of defect sites on the surface of the carrier, so that the metal single atom has relatively high loading capacity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of catalyst preparation, and in particular to a supported single-atom catalyst and a preparation method and application thereof. Background Art

[0002] In the current global context of energy conservation and carbon emissions control, the importance of precious metal nanocatalysts in various catalytic reactions is increasing day by day. Due to their scarcity and high price, people have been working on reducing their size, improving their dispersibility and optimizing their intrinsic activity. Compared with nanoparticles, single atom catalysts (SACs) have unique advantages, including good uniformity of active sites, small coordination number of active center atoms, atomic utilization close to 100%, a wide range of catalyst supports, precise structural design and low precious metal usage.

[0003] In single-atom catalysts, due to the high surface free energy of atoms, they tend to aggregate into nanoparticles or nanoclusters, which reduces the catalytic activity. In order to prevent the movement and aggregation of atoms, it is necessary to select a suitable carrier to form a strong interaction with the single atoms, so as to obtain a stable single-atom active site. Many strategies have been proposed to solve this problem, including the use of confinement effects (such as metal organic frameworks), the formation of chemical bonds (MN x C y ), or modifying the support material to introduce defects and vacancies to enhance and stabilize the interaction between metal atoms and the support material, but the number of these sites is often limited, resulting in a low single-atom loading capacity. Summary of the invention

[0004] In order to solve the above technical problems, the present invention provides a method for preparing a supported single-atom catalyst, comprising the following steps:

[0005] The nanoporous metal oxide is immersed in a precursor solution of a metal salt to obtain a metal salt supported on the nanoporous metal oxide; the metal salt supported on the nanoporous metal oxide is heat-treated to decompose and obtain a metal single atom catalyst supported on the nanoporous metal oxide.

[0006] Preferably, the method for preparing the nanoporous metal oxide comprises:

[0007] growing metal hydroxide / oxyhydroxide nanosheets on the surface of the substrate by electrochemical deposition;

[0008] The metal hydroxide / oxyhydroxide nanosheets are heat treated to decompose and obtain nanoporous metal oxides.

[0009] Preferably, before growing the metal hydroxide / oxyhydroxide nanosheets on the surface of the substrate, the surface of the substrate is pickled to remove oxides or increase hydrophilicity.

[0010] Preferably, the substrate is carbon paper, carbon cloth, nickel mesh or foam material, and the foam material is foam nickel, foam copper, foam nickel iron, foam titanium, foam stainless steel or foam carbon;

[0011] When the substrate is carbon paper or carbon cloth, the surface of the substrate is hydrophilized by nitric acid; when the substrate is a nickel mesh or foam material, the surface of the substrate is degreased by acetone and pickled with hydrochloric acid to remove oxides, the mesh number of the nickel mesh is 10 to 400 meshes, and the pore number of the foam material is 5 to 130 ppi.

[0012] Preferably, the method for growing metal hydroxide / oxyhydroxide nanosheets on the surface of a substrate by electrochemical deposition comprises:

[0013] The substrate is used as a working electrode and placed in an electrochemical system of a three-electrode system for electrochemical deposition, and metal hydroxide / oxyhydroxide nanosheets are grown on the surface of the substrate.

[0014] Preferably, the metal hydroxide / oxyhydroxide nanosheets are Co(OH)2, Ni(OH)2 or FeOOH.

[0015] Preferably, in the heat treatment of the metal hydroxide / oxyhydroxide nanosheets, the heat treatment temperature is 300-400° C., the heat treatment time is 0.5-3 h, and the heat treatment gas atmosphere is argon or air.

[0016] Preferably, the precursor of the metal salt is a metal chloride salt.

[0017] Preferably, the metal chloride salt is chloroplatinic acid, chloroiridic acid, ruthenium chloride, nickel chloride, ferric chloride, cupric chloride or cobalt chloride, and the metal single atom is platinum, iridium, ruthenium, nickel, iron, copper or cobalt.

[0018] Preferably, the precursor concentration in the metal salt precursor solution is 1-100 mmol / L, and the immersion time is 1-20 min.

[0019] Preferably, in the heat treatment of the metal salt supported on the nanoporous oxide, the heat treatment temperature is 50 to 350° C., the heat treatment time is 1 to 180 min, and the heat treatment atmosphere is argon or air.

[0020] The present invention also provides a supported single-atom catalyst prepared according to the above method, comprising a metal single-atom catalyst supported on the nanoporous metal oxide.

[0021] The present invention also provides a supported single-atom catalyst for use as a water electrolysis catalyst.

[0022] Compared with the prior art, the technical solution of the embodiment of the present invention has the following beneficial effects:

[0023] The present invention immerses nanoporous metal oxide in a precursor solution of a metal salt to obtain a metal salt loaded on the nanoporous metal oxide, and heat treats the metal salt loaded on the porous metal oxide so that the chemical bonds on the surface of the metal atoms are not completely broken, and the metal atoms are kept in a relatively isolated state to form single atoms. At the same time, the metal atoms are anchored by bonding with oxygen on the surface of the nanoporous metal oxide carrier. The metal single atoms formed by this method rely on the incompletely broken chemical bonds on the surface for isolation, and do not rely on the number of defect sites on the carrier surface, so it has a higher loading capacity. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.

[0025] Figure 1 This is a low-magnification scanning electron microscope image of Ir-SA / Co3O4-250 prepared in Example 1 of the present invention;

[0026] Figure 2 This is a high-magnification scanning electron microscope image of Ir-SA / Co3O4-250 prepared in Example 1 of the present invention;

[0027] Figure 3 This is a low-magnification scanning transmission electron microscopy image of Ir-SA / Co3O4-250 prepared in Example 1 of the present invention;

[0028] Figure 4 This is a high-resolution scanning transmission electron microscopy image of Ir-SA / Co3O4-250 prepared in Example 1 of the present invention;

[0029] Figure 5 This is a high-resolution scanning transmission electron microscopy image of Pt-SA / Co3O4-250 prepared in Example 2 of the present invention;

[0030] Figure 6This is a high-resolution scanning transmission electron microscopy image of Ru-SA / Co3O4-250 prepared in Example 3 of the present invention;

[0031] Figure 7 This is a high-resolution scanning transmission electron microscopy image of Ir-SA / Fe2O3-250 prepared in Example 4 of the present invention;

[0032] Figure 8 X-ray diffraction patterns of different samples in Example 1 and Comparative Example 1 of the present invention;

[0033] Fig. 9 Polarization curves of Ir-SA / Co3O4-T samples prepared at different annealing temperatures in Example 1 of the present invention and Comparative Example 1 in 1.0M KOH electrolyte;

[0034] Fig.10 Polarization curves of Ir-SA / Co3O4-250 samples prepared by annealing at 250° C. for different times in Example 1 of the present invention and Comparative Example 2 in 1.0 M KOH electrolyte;

[0035] Fig.11 This is a high-resolution scanning transmission electron microscopy image of Ir-NC / Co3O4-250 prepared in Comparative Example 3 of the present invention;

[0036] Fig.12 Polarization curves of different samples in Example 1 and Comparative Example 3 of the present invention in 1.0M KOH electrolyte;

[0037] Fig.13 This is a high-resolution scanning transmission electron microscopy image of Pt-NC / Co3O4-250 prepared in Example 4 of the present invention;

[0038] Fig.14 Polarization curves of different samples in Example 2 and Comparative Example 4 of the present invention in 1.0M KOH electrolyte;

[0039] Fig.15 This is a high-resolution scanning transmission electron micrograph of Ru-NC / Co3O4-250 prepared in Example 5 of the present invention. DETAILED DESCRIPTION

[0040] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0041] The terms "first", "second", "third", "fourth", etc. (if any) in the specification and claims of the present invention and the above-mentioned drawings are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequence. It should be understood that the data used in this way can be interchanged where appropriate, so that the embodiments of the present invention described herein can be implemented in an order other than those illustrated or described herein. In addition, the terms "including" and "having" and any variations thereof are intended to cover non-exclusive inclusions, for example, a process, method, system, product or device that includes a series of steps or units is not necessarily limited to those steps or units that are clearly listed, but may include other steps or units that are not clearly listed or inherent to these processes, methods, products or devices.

[0042] As described in the background art, in existing single-atom catalysts, the loading of single atoms is low.

[0043] In order to solve the above technical problems, the present invention provides a method for preparing a supported single-atom catalyst, comprising the following steps:

[0044] The nanoporous metal oxide is immersed in a precursor solution of a metal salt to obtain a metal salt supported on the nanoporous metal oxide; the metal salt supported on the nanoporous metal oxide is heat-treated to decompose and obtain a metal single atom catalyst supported on the nanoporous metal oxide.

[0045] The present invention immerses nanoporous metal oxide in a precursor solution of a metal salt to obtain a metal salt loaded on the nanoporous metal oxide, and heat treats the metal salt loaded on the porous metal oxide so that the chemical bonds on the surface of the metal atoms are not completely broken, and the metal atoms are kept in a relatively isolated state to form single atoms. At the same time, the metal atoms are anchored by bonding with oxygen on the surface of the nanoporous metal oxide carrier. The metal single atoms formed by this method rely on the incompletely broken chemical bonds on the surface for isolation, and do not rely on the number of defect sites on the carrier surface, so it has a higher loading capacity.

[0046] The present invention does not limit the preparation method of the nanoporous metal oxide. A hydrothermal method, a solution method or an electrochemical deposition method can be used to first prepare metal hydroxide / hydroxy oxide nanosheets, or metal basic carbonate nanoparticles or nanorods, and then the metal oxide remaining after the water or carbon dioxide in the material is volatilized by heat treatment such as calcination in the air has a nanoporous structure, thereby obtaining a metal oxide with a nanoporous structure.

[0047] As an embodiment, a method for preparing nanoporous metal oxide by electrochemical deposition includes:

[0048] growing metal hydroxide / oxyhydroxide nanosheets on the surface of the substrate by electrochemical deposition;

[0049] The metal hydroxide / oxyhydroxide nanosheets are heat treated to decompose and obtain nanoporous metal oxides.

[0050] Furthermore, before growing the metal hydroxide / oxyhydroxide nanosheets on the surface of the substrate, the surface of the substrate is pickled to remove oxides or increase hydrophilicity.

[0051] In the method of preparing nanoporous metal oxide by electrochemical deposition, the present invention does not limit the specific material and structure type of the substrate, such as carbon paper, carbon cloth, nickel mesh or foam material, and the foam material is foam nickel, foam copper, foam nickel iron, foam titanium, foam stainless steel or foam carbon.

[0052] When the substrate is carbon paper or carbon cloth, the surface of the substrate is hydrophilized by nitric acid; when the substrate is a nickel mesh or foam material, the surface of the substrate is degreased by acetone and pickled with hydrochloric acid to remove oxides, the mesh number of the nickel mesh is 10 to 400 meshes, and the pore number of the foam material is 5 to 130 ppi.

[0053] Furthermore, the substrate is used as a working electrode and placed in a three-electrode electrochemical system for electrochemical deposition, and metal hydroxide / oxyhydroxide nanosheets are grown on the surface of the substrate.

[0054] In the heat treatment of the metal hydroxide / oxyhydroxide nanosheets, the heat treatment temperature is preferably 300-400° C., the heat treatment time is preferably 0.5-3 h, and the heat treatment gas atmosphere is preferably argon or air.

[0055] In order to synthesize SACs with a higher metal single atom loading and still maintain stability, the present invention selects metal chloride salts as metal precursors, and the metal chloride salts can be chloroplatinic acid, chloroiridic acid, ruthenium chloride, nickel chloride, ferric chloride, copper chloride or cobalt chloride, so that the corresponding metal single atoms are platinum, iridium, ruthenium, nickel, iron, copper or cobalt. In the heat treatment of the metal salt supported on the nanoporous oxide, the heat treatment temperature is 50-350°C, the heat treatment time is 1-180min, and the heat treatment atmosphere is argon or air, that is, the appropriate synthesis temperature is used to incompletely break the chemical bonds on the surface of the metal atoms, so that the metal atoms are kept in a relatively isolated state to form single atoms, and at the same time, the metal atoms are anchored by bonding with oxygen on the surface of the metal oxide carrier. The metal single atoms formed by this method rely on the incompletely broken chemical bonds on the surface for isolation, and do not rely on the number of defect sites on the surface of the carrier, so they have a higher loading capacity.

[0056] In order to make the above-mentioned purposes, features and beneficial effects of the present invention more obvious and understandable, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0057] Embodiment 1:

[0058] This embodiment prepares a supported single-atom catalyst, which is an iridium single-atom catalyst supported on a cobalt oxide carrier (Ir-SA / Co3O4-250), and its preparation method specifically includes the following steps:

[0059] (1) Soak a 1×1.5 cm carbon paper in a 70° C. 8.0 M nitric acid solution for 6 h, cool it, rinse it with deionized water to obtain a hydrophilic carbon paper, and soak it in deionized water for storage.

[0060] (2) A cobalt nitrate solution with a concentration of 0.1 M was prepared and electrochemical deposition was performed using a three-electrode system.

[0061] The working electrode is the carbon paper treated with hydrophilicity in step (1), the reference electrode is a mercury / mercuric oxide reference electrode, and the counter electrode is a carbon rod electrode. Deposition is performed at a constant voltage of -0.9 V for 500 s. After the deposition, the carbon paper deposited with α-Co(OH)2 is dried at 50°C.

[0062] (3) The carbon paper on which α-Co(OH)2 was deposited in step (2) was annealed at 350°C for 2 h in an air atmosphere to obtain nanoporous Co3O4 supported on the carbon paper.

[0063] (4) The nanoporous Co3O4 obtained in step (3) was soaked in a 20 mM chloroiridic acid solution for 5 min, then taken out and dried at 50° C. The obtained composite material was calcined at 250° C. for 60 min in an air atmosphere to obtain Ir-SA / Co3O4-250, wherein Ir accounts for about 3 at.% of the metal atoms in the whole material and about 7.2 wt.% of the weight of the whole material.

[0064] Figure 1 This is a low-magnification scanning electron microscope image of the obtained Ir-SA / Co3O4-250 catalyst. It can be seen that the catalyst is Co3O4 grown in a nanosheet structure. The size of the nanosheet is about 0.5-1μm, the distance between the sheets is about 0.3-0.4μm, and the growth substrate is carbon paper.

[0065] Figure 2This is a high-magnification scanning electron microscope of the obtained Ir-SA / Co3O4-250 catalyst, in which Co3O4 exists in a nanoporous form and obvious pore structure can be seen on the surface of the nanosheets.

[0066] Figure 3 This is the scanning transmission electron microscopy image of the obtained Ir-SA / Co3O4-250 catalyst. It can be seen that the nanoporous structure of Co3O4 is obvious, and the overall brightness of Co3O4 is uniform, without obvious aggregation of nanoparticles, indicating that Ir single atoms are evenly distributed on the surface of Co3O4.

[0067] Figure 4 This is a high-resolution scanning transmission electron micrograph of the obtained Ir-SA / Co3O4-250 catalyst, in which the bright spots are single Ir atoms, which have a high single atom density on the surface of the Co3O4 carrier and are randomly distributed as a whole, independent of the surface structure of Co3O4.

[0068] Embodiment 2:

[0069] In this embodiment, a supported single-atom catalyst is prepared, which is a platinum single-atom catalyst supported on a cobalt tetroxide carrier (Pt-SA / Co3O4-250). The difference between its preparation method and that of Example 1 is that the solution used for immersion in step (4) is different. In this embodiment, 20 mM chloroplatinic acid is used.

[0070] Figure 5 This is a high-resolution scanning transmission electron microscopy image of the obtained Pt-SA / Co3O4-250 catalyst. It can be observed that Pt is mainly distributed on the surface of the Co3O4 carrier in the form of single atoms.

[0071] Embodiment 3:

[0072] In this embodiment, a supported single-atom catalyst is prepared, which is a ruthenium single-atom catalyst supported on a cobalt tetroxide carrier (Ru-SA / Co3O4-250). The difference between its preparation method and that of Example 1 is that the solution used for immersion in step (4) is different. In this embodiment, 20 mM ruthenium chloride is used.

[0073] Figure 6 This is a high-resolution scanning transmission electron microscopy image of the obtained Ru-SA / Co3O4-250 catalyst. It can be observed that Ru is mainly distributed on the surface of the Co3O4 carrier in the form of single atoms.

[0074] Embodiment 4:

[0075] This embodiment prepares a supported single-atom catalyst, which is an iridium single-atom catalyst supported on a ferric oxide carrier (Ir-SA / Fe2O3-250). Its preparation method is different from that of Example 1 in terms of the preparation method of the oxide carrier in steps (2) and (3).

[0076] Step (2) of this embodiment is: using a three-electrode system with a 1×1 cm 2 The hydrophilic treated carbon paper was used as the anode, the carbon rod as the cathode, and the silver / silver chloride as the reference electrode to electrodeposit FeOOH nanosheets on the carbon paper. The electrolyte solution consisted of 0.1M Na2SO4, 0.2M CH3COONa, and 0.1MFe(NH4)2(SO4)2·6H2O. The charge was charged at 1.25 mA / cm 2 FeOOH was electro-deposited at a constant current density of 1000 nm for 10 min. Finally, the carbon paper with FeOOH deposited was washed with deionized water and dried in air at 50 °C.

[0077] Step (3) of this embodiment is: annealing the carbon paper on which FeOOH is deposited in step (2) at 350° C. for 2 h in an air atmosphere to obtain nanoporous Fe2O3 loaded on the carbon paper.

[0078] Figure 7 This is a high-resolution scanning transmission electron microscopy image of the obtained Ir-SA / Fe2O3-250 catalyst. It can be observed that Ir is mainly distributed on the surface of the Fe2O3 carrier in the form of single atoms.

[0079] Comparative Example 1:

[0080] The difference between this comparative example and Example 1 is that in this comparative example, the calcination temperature in step (4) in Example 1 is changed from 250°C to 50°C, 150°C and 350°C, and the obtained single atom catalysts are Ir-SA / Co3O4-50, Ir-SA / Co3O4-150 and Ir-SA / Co3O4-350 respectively.

[0081] Figure 8 Figure 2 shows the X-ray diffraction patterns of Ir-SA / Co3O4 samples obtained at different heat treatment temperatures. No XRD peak of Ir species was found in different Ir-SA / Co3O4 samples, indicating that no obvious Ir or IrO2 particles were generated, and the peak position of Co3O4 remained unchanged, indicating that Ir was only distributed in the outermost layer of Co3O4 and did not enter the Co3O4 lattice.

[0082] Fig. 9Figure 2 shows the polarization curves of oxygen evolution reaction of Ir-SA / Co3O4 samples obtained at different heat treatment temperatures in 1.0 M KOH electrolyte. Among the samples obtained at various heat treatment temperatures, Ir-SA / Co3O4-250 exhibits the best catalytic activity at a current density of 10 mA / cm 2 When , the overpotentials of each sample are: Co3O4 (347mV), Ir-SA / Co3O4-50 (341mV), Ir-SA / Co3O4-150 (258mV), Ir-SA / Co3O4-150 (220mV) and Ir-SA / Co3O4-350 (263mV).

[0083] Comparative Example 2:

[0084] The difference between this comparative example and Example 1 is that the calcination time in step (4) in Example 1 is changed from 60 min to 1 min, 10 min, 30 min and 120 min in this comparative example, and the obtained single atom catalysts are Ir-SA / Co3O4-250 1 min, Ir-SA / Co3O4-250 10 min, Ir-SA / Co3O4-250 30 min and Ir-SA / Co3O4-250 120 min respectively.

[0085] Fig.10 The polarization curves of the oxygen evolution reaction of Ir-SA / Co3O4 samples obtained by heat treatment at 250℃ for different times in 1.0MKOH electrolyte show that the single atom is formed very quickly. After annealing for 10 minutes, the starting potential of the sample polarization curve tends to be stable. After continuing annealing for 60 minutes, the catalytic performance of the sample reaches the optimal level.

[0086] Comparative Example 3:

[0087] This comparative example prepares a nanocluster catalyst, which is an iridium nanocluster catalyst supported on cobalt tetroxide (Ir-NC / Co3O4-250). The difference compared with Example 1 is that the solution used for soaking in step (4) of this comparative example is 20 mM iridium acetate.

[0088] Fig.11 This is a high-resolution scanning transmission electron microscopy image of the obtained Ir-NC / Co3O4-250 catalyst. Ir exists mainly in the form of clusters on the Co3O4 surface and is unevenly distributed.

[0089] Fig.12 Polarization curve of oxygen evolution reaction of Ir-NC / Co3O4-250 catalyst in 1.0M KOH electrolyte at 10mA / cm 2The overpotential at the current density is 253 mV, which is 33 mV higher than that of the Ir-SA / Co3O4-250 catalyst prepared under the same heat treatment conditions in Example 1.

[0090] Comparative Example 4:

[0091] This comparative example prepares a nanocluster catalyst, which is a platinum nanocluster catalyst supported on cobalt tetroxide (Pt-NC / Co3O4-250). The difference compared with Example 1 is that the solution used for immersion in step (4) of this comparative example is 20 mM platinum nitrate.

[0092] Fig.13 This is a high-resolution scanning transmission electron microscopy image of the obtained Pt-NC / Co3O4-250 catalyst. Pt mainly exists in the form of clusters on the Co3O4 surface.

[0093] Fig.14 Polarization curves of the single atom catalyst Pt-SA / Co3O4-250 prepared in Example 2 and the nanocluster catalyst Pt-NC / Co3O4-250 prepared in Comparative Example 4 in the hydrogen evolution reaction in 1.0 M KOH electrolyte at a current density of 10 mA / cm 2 When , the overpotential of Pt-SA / Co3O4-250 catalyst is 42 mV, while the overpotential of Pt-NC / Co3O4-250 catalyst is 61 mV.

[0094] Comparative Example 5:

[0095] This comparative example prepares a nanocluster catalyst, which is a ruthenium nanocluster catalyst supported on cobalt tetroxide (Ru-NC / Co3O4-250). The difference compared with Example 1 is that the solution used for soaking in step (4) of this comparative example is 20mM ruthenium nitrosonitrate.

[0096] Fig.15 This is a high-resolution scanning transmission electron microscopy image of the obtained Ru-NC / Co3O4-250 catalyst. Ru mainly exists in the form of clusters on the Co3O4 surface.

[0097] It can be seen from Comparative Examples 3 to 5 that metal single atoms cannot be prepared from metal salt precursors that do not contain chlorine.

[0098] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing a supported single-atom catalyst, characterized in that: The following steps are involved: The nanoporous metal oxide is immersed in a precursor solution of the metal salt to obtain a metal salt supported on the nanoporous metal oxide; The metal salt supported on the nanoporous metal oxide is heat-treated to decompose and obtain a metal single-atom catalyst supported on the nanoporous metal oxide.

2. The method for preparing a supported single-atom catalyst according to claim 1, characterized in that: The preparation method of the nanoporous metal oxide comprises: growing metal hydroxide / oxyhydroxide nanosheets on the surface of the substrate by electrochemical deposition; The metal hydroxide / oxyhydroxide nanosheets are heat treated to decompose and obtain nanoporous metal oxides.

3. The method for preparing a supported single-atom catalyst according to claim 2, characterized in that: Before growing metal hydroxide / oxyhydroxide nanosheets on the surface of the substrate, the surface of the substrate is subjected to an acid wash treatment to remove oxides or increase hydrophilicity.

4. The method for preparing a supported single-atom catalyst according to claim 3, characterized in that: The substrate is carbon paper, carbon cloth, nickel mesh or foam material, and the foam material is foam nickel, foam copper, foam nickel iron, foam titanium, foam stainless steel or foam carbon; When the substrate is carbon paper or carbon cloth, the surface of the substrate is hydrophilized by nitric acid; when the substrate is a nickel mesh or foam material, the surface of the substrate is degreased by acetone and pickled with hydrochloric acid to remove oxides, the mesh number of the nickel mesh is 10 to 400 meshes, and the pore number of the foam material is 5 to 130 ppi.

5. The method for preparing a supported single-atom catalyst according to claim 2, characterized in that: The method for growing metal hydroxide / oxyhydroxide nanosheets on the surface of a substrate by electrochemical deposition comprises: The substrate is used as a working electrode and placed in an electrochemical system of a three-electrode system for electrochemical deposition, and metal hydroxide / oxyhydroxide nanosheets are grown on the surface of the substrate.

6. The method for preparing a supported single-atom catalyst according to claim 2, characterized in that: The metal hydroxide / oxyhydroxide nanosheet is Co(OH)2, Ni(OH)2 or FeOOH.

7. The method for preparing a supported single-atom catalyst according to claim 2, characterized in that: In the heat treatment of the metal hydroxide / oxyhydroxide nanosheets, the heat treatment temperature is 300-400° C., the heat treatment time is 0.5-3 hours, and the heat treatment gas atmosphere is argon or air.

8. The method for preparing a supported single-atom catalyst according to claim 1, characterized in that: The precursor of the metal salt is a metal chloride salt.

9. The method for preparing a supported single-atom catalyst according to claim 8, characterized in that: The metal chloride salt is chloroplatinic acid, chloroiridic acid, ruthenium chloride, nickel chloride, ferric chloride, copper chloride or cobalt chloride, and the metal single atom is platinum, iridium, ruthenium, nickel, iron, copper or cobalt.

10. The method for preparing a supported single-atom catalyst according to claim 1, characterized in that: The precursor concentration in the metal salt precursor solution is 1-100 mmol / L, and the immersion time is 1-20 minutes.

11. The method for preparing a supported single-atom catalyst according to claim 1, characterized in that: In the heat treatment of the metal salt supported on the nanoporous oxide, the heat treatment temperature is 50 to 350° C., the heat treatment time is 1 to 180 min, and the heat treatment atmosphere is argon or air. 12 . The supported single-atom catalyst prepared by the method according to claim 1 , comprising a metal single-atom catalyst supported on the nanoporous metal oxide.

13. Use of the supported single-atom catalyst according to claim 12 as a water electrolysis catalyst.

Citation Information

Patent Citations

  • Method for preparing monatomic catalyst

    CN110743566A

Cited By

  • Foamy carbon-based chlorine-nitrogen co-coordinated monatomic catalyst and application thereof in killing drug-resistant bacteria in water

    CN121372502A

  • A foam carbon-based chlorine-nitrogen co-coordination monatomic catalyst and application thereof to killing drug-resistant bacteria in water

    CN121372502B